2012
DOI: 10.1590/s0100-69162012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Several regulations in gravity table in quality of tobacco seeds

Abstract: ABSTRACT:The use of gravity table can result in improved quality of seeds of several species, demonstrating the superiority of the quality attributes of seeds collected in the top positions in relation to the lower positions of the discharge zone of the gravity table. The availability of information on tobacco seeds, particularly on the action of gravity table, has not been addressed in the literature. The present study was to evaluate the influence of different regulations in the gravity table on the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Eventually, they also found that seeds classified by the densimetric table had higher mass of one thousand seeds rates. Endorsing these observations, Gadotti et al (2012) declared that it was possible to obtain highquality seeds from those distributed at the top parts of the table.…”
Section: Resultsmentioning
confidence: 98%
“…Eventually, they also found that seeds classified by the densimetric table had higher mass of one thousand seeds rates. Endorsing these observations, Gadotti et al (2012) declared that it was possible to obtain highquality seeds from those distributed at the top parts of the table.…”
Section: Resultsmentioning
confidence: 98%
“…It was possible to see a statistically significant stratification by weight within this lot for the different seed classes from the outlets of the densimetric table, demonstrating the efficiency of the gravitational table for separating by weight and/ or density. Gadotti et al (2012) commented that it was possible to obtain higher quality seeds from those distributed to the upper areas of the densimetric The results from the germination test show that those seeds from the first germination count collected from the highest part of the densimetric table were significantly more vigorous ( Table 2). The percentage germination of seeds from the upper outlets was also high compared to the other classifications, demonstrating the efficiency of the table for cleaning castor bean seeds.…”
Section: Resultsmentioning
confidence: 99%
“…The lower discharge of the gravitational table usually separates P. maximum seeds (Melo et al, 2016a(Melo et al, , 2016b and Nicotiana tabacum seeds (Gadotti et al, 2012) that have a smaller dry mass, lower germination rate, and less vigor. For several species, it was found that seeds with these characteristics are more susceptible to attack by Fusarium sp.…”
Section: Resultsmentioning
confidence: 99%